Islamic Education and Freirean Critical Pedagogy: Reconstructing Justice and Liberation in Multicultural Contexts - Alwy Ahmed Mohamed; Aya Ragab (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study seeks to examine how Paulo Freire’s theory of critical pedagogy can be reinterpreted through the lens of Islamic educational philosophy in order to promote justice, emancipation, and transformative learning in modern education. Specifically, it explores the alignment between Freirean concepts of dialogue, conscientization, and the rejection of the “banking model” of education and key Islamic educational values such as tarbiyah, ‘adl, and shura. Theoretical framework: The study is grounded in Paulo Freire’s critical pedagogy and Islamic educational philosophy. Freire’s framework emphasizes education as a practice of freedom aimed at raising critical consciousness and challenging oppression, while Islamic educational philosophy stresses moral formation, social justice, community responsibility, and spiritual development. Literature review: Existing scholarship on critical pedagogy highlights Freire’s influence on emancipatory education, social justice, and resistance to hegemonic power structures. Meanwhile, literature on Islamic education emphasizes holistic human development, ethical responsibility, and communal well-being. Method: This study employs a qualitative methodology based on literature review and textual analysis. Key writings by Paulo Freire are compared with classical and contemporary Islamic educational texts to identify convergences and divergences in their philosophical foundations, pedagogical aims, and approaches to justice and emancipation. Results: The findings indicate that Islamic educational philosophy offers a liberatory framework that complements and deepens Freire’s critical pedagogy. Islamic concepts provide a spiritual and ethical foundation that reinforces Freire’s emphasis on dialogue, critical awareness, and social transformation, while also addressing moral formation and communal responsibility. Implications: The study underscores the potential of integrating Islamic educational philosophy with Freirean pedagogy to enhance critical consciousness, promote justice, and foster community empowerment. Such integration can support educators in developing transformative educational practices rooted in ethics, spirituality, and social responsibility. Novelty: The novelty of this study lies in its interdisciplinary synthesis of critical pedagogy and Islamic educational philosophy, offering an alternative model of transformative education that unites emancipation, ethical grounding, and collective empowerment.